The Immunisation Dilemma—Part 6: Towards Agreement on Homeoprophylaxis - Golden, Isaac (Homœopathic Links, 2016)
This paper restates a majority position on homeoprophylaxis (HP) determined through two international surveys of homeopaths. It examines the use of HP around the world and discusses the main points of contention. The need for more research into the safety and effectiveness of HP is highlighted, as is the need to improve the education about HP in Colleges around the world. In the end, Hahnemann's contribution to the prevention of infectious diseases is found to have stood the test of time, but not without difficulties or controversy. Yet HP remains a valuable asset in the classic homeopath's toolkit of safe and effective medicines.
Keywords: homeoprophylaxis; majority position; evidence; education